Longitudinal surveillance of Aedes aegypti (Diptera: Culicidae) in urban coastal Kenya: population dynamics, blood feeding frequency and dengue virus infection rates - Josephine Osalla; Louis-Clement Gouagna; Gilbert Rotich; Maureen Nzilani; Penina Safari; Kennedy Senagi; Francis Mutuku; Baldwyn Torto; David P. Tchouassi (Scientific Reports)
Abstract The coastal region of Kenya has emerged as a focal point for urban dengue virus transmission driven by Aedes aegypti as the primary vector. To gain a deeper understanding of the epidemiological situation, we carried out a year-long longitudinal study (December 2021- November 2022) of the population dynamics of A. aegypti through weekly mosquito surveys using ovitrap and CO2-baited Biogents (BG) mosquito traps in Ukunda, an urban township in the coastal region. Aedes eggs laid in ovitraps were exclusively A. aegypti with 80.8% mean hatch rate. A total of 35,109 adult A. aegypti were captured, with twice as many females than males. The density of adult A. aegypti trap captures varied monthly, but there was no discernible delineation by season. Aedes aegypti fed more on humans (human blood index = 0.72). Two dengue-2 virus RNA was detected in two blood-fed specimens that had fed on humans. Multiple linear regression model indicated 59% variation in adult female abundance explained by weather variables including daily range in wind speed (82.9%) and temperature (17.1%). In contrast, random forest model revealed 83% variation in egg abundance attributed to weather variables, being positively influenced by mean daily temperature, wind speed, relative humidity and negatively by total precipitation. Our results confirm year-round vector presence and active circulation of dengue virus indicative of endemicity in urban Kenya. The findings highlight the importance of short-term climatic factors as predictors of A. aegypti dynamics of value in surveillance and control of arboviral diseases such as dengue.